2018
DOI: 10.3168/jds.2018-14587
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of subclinical hypocalcemia in early-lactation Holstein dairy cows: The temporal associations of plasma calcium concentration in the first 4 days in milk with disease and milk production

Abstract: The objectives of this study were to characterize the epidemiology of subclinical hypocalcemia (SCH) in Holstein dairy cows by assessing the temporal associations of plasma Ca concentrations in the first 4 d in milk (DIM) with the risk of cows being diagnosed with metritis or displaced abomasum (or both), and milk production across the first 15 wk of lactation. A prospective cohort study was conducted in 2 dairy herds in New York State, in which cows had a blood sample collected daily for the first 4 DIM. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 31 publications
7
88
1
3
Order By: Relevance
“…The sample size available to assess the treatment by serum calcium concentration effect, as well as the degree of hypocalcemia in the study herds may have limited the power of the present study to detect the effects of serum calcium concentration before supplementation on treatment response. Recent research suggests that the time relative to parturition when blood calcium concentration is assessed plays a role on its association with productive and health outcomes (Neves et al, 2018); thus, it is plausible that the serum calcium concentration assessed within the first 5 h following parturition may not have the strongest association with the evaluated productive and reproductive outcomes. In addition, the improved calcemia following oral calcium supplementation observed in the former study by our group was only evident up to 2 DIM (Valldecabres et al, 2018); the limited size or absence of effects observed for the evaluated productive and reproductive outcomes may also indicate that calcemia within the first 48 h following parturition may not be strongly associated with the evaluated outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size available to assess the treatment by serum calcium concentration effect, as well as the degree of hypocalcemia in the study herds may have limited the power of the present study to detect the effects of serum calcium concentration before supplementation on treatment response. Recent research suggests that the time relative to parturition when blood calcium concentration is assessed plays a role on its association with productive and health outcomes (Neves et al, 2018); thus, it is plausible that the serum calcium concentration assessed within the first 5 h following parturition may not have the strongest association with the evaluated productive and reproductive outcomes. In addition, the improved calcemia following oral calcium supplementation observed in the former study by our group was only evident up to 2 DIM (Valldecabres et al, 2018); the limited size or absence of effects observed for the evaluated productive and reproductive outcomes may also indicate that calcemia within the first 48 h following parturition may not be strongly associated with the evaluated outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological response to transient hypocalcaemia is an increase in bone mobilisation followed by enhanced gastrointestinal absorption (van´t Klooster, 1976). If these mechanisms are compromised, either the extent or the duration of hypocalcaemia is exacerbated resulting in increased risks of developing different diseases in early lactation depending on the duration of hypocalcaemia (Neves et al, 2018). Reliable data on the prevalence of peripartum hypocalcaemia in small ruminants are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…All of these disorders have adverse effects on animal welfare, milk production, reproduction, and farm profitability [9,10].…”
Section: Introductionmentioning
confidence: 99%